Investigating the Effects of Coenzyme Q10 on Human Corneal Endothelial Cells. (13th August 2021) - Titley, Mitchell; Ahmad, Sajjad; Parekh, Mohit
Abstract : Purpose . To investigate the effects of Coenzyme Q10 (CoQ10) treatment on immortalised human corneal endothelial cells (HCEC-12). Methods . HCEC-12 cells were cultured in different concentrations of CoQ10 (0.1%, 0.2%, 0.5%, and 1.0%) and analysed using live/dead staining assay to determine appropriate concentration for subsequent experiments. Cells were pretreated with CoQ10 before inducing apoptosis by ethanol (EtOH) treatment for 30 seconds which was followed by posttreatment with CoQ10. Viable, apoptotic, and dead cell proportions were analysed using Annexin V-FITC immunofluorescence staining. Mitochondrial intensity and respiratory functions were also investigated using MitoTracker staining and a Seahorse XFe24 analyser, respectively. Results were compared to a positive control for apoptosis. The experiments were carried out in triplicates. Graphpad prism software was used for statistical analysis where p < 0.05 was deemed statistically significant. Results . CoQ10 treatment at 0.5% and 1% showed 92% and 30% viable cells compared with 0.1% and 0.2% that showed 96% and 94% viable cells, respectively (p = 0.0562 ). 0.1% and 0.2% concentrations were, thus, used for subsequent experiments. Annexin V-FITC apoptotic analysis showed 2% at 0.1% and 3% at 0.2% of apoptotic cells (p = 0.0824 ). Mitochondrial respiratory function and mitochondrial intensity increased in apoptotic cells following 0.1% CoQ10 treatment. Conclusion . 0.1% CoQ10 was found optimal for reducing apoptosis and increasing metabolic activity on human corneal endothelial cell line. These results support the need for further ex vivo studies to investigate the safety profile of CoQ10 as an antiapoptotic agent for human corneal endothelium.